2016
DOI: 10.1002/cben.201500018
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Metal and Metal Oxide Nanoparticles

Abstract: Bioresource‐based green synthesis of nanoparticles has gained significant interest as an emerging technology to reduce the toxicity of nanoparticles commonly associated with conventional chemical synthesis approaches. Studies on green synthesis of metal nanoparticles have been carried out with various biological materials including from bacteria, fungi, and plant extracts. Plant extracts in particular have been extensively used for the synthesis of metal and metal oxide nanoparticles, and this is due to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 256 publications
(108 citation statements)
references
References 220 publications
0
96
0
Order By: Relevance
“…On introduction of the plant extract, the active phytochemicals reduced the metal cations into zerovalent ions, which agglomerates into NPs due to lack of interatomic repulsion. The exact method of metal oxide NPs formation is not exactly understood, but it is suggested that they are formed due to oxidation of metal NPs with atmospheric oxygen or decomposition of phytochemicals . Figure (b) is a schematic representation of the formation of NiO NPs from the precursor nickel acetate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On introduction of the plant extract, the active phytochemicals reduced the metal cations into zerovalent ions, which agglomerates into NPs due to lack of interatomic repulsion. The exact method of metal oxide NPs formation is not exactly understood, but it is suggested that they are formed due to oxidation of metal NPs with atmospheric oxygen or decomposition of phytochemicals . Figure (b) is a schematic representation of the formation of NiO NPs from the precursor nickel acetate.…”
Section: Resultsmentioning
confidence: 99%
“…The exact method of metal oxide NPs formation is not exactly understood, but it is suggested that they are formed due to oxidation of metal NPs with atmospheric oxygen or decomposition of phytochemicals. [11] Fig…”
Section: Synthesis and Characterization Of Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations